담도암 수술 중 발견된 담석성 회장천공 - 조부관(Bugoan Cho); 최영일(Youngil Choi); 신동훈(Donghoon Shin) (Annals of surgical treatment and research, 2007)
Gallstone is a common disease with a prevalence of about 10%, but biliary ileus is a rare entity with a frequency of about 1% for all the symptomatic patients. We are reporting on a case of perforated terminal ileum that was due to gallstone, and this was without any associated intestinal obstruction or bilioenteric fistula. A 76 year old man presented with a history of jaundice and dark colored urine for a 3-month duration with no clinical features of intestinal obstruction. There was no past history of biliary tract disease. The abdominal radiograph demonstrated no biliary stones or classical findings of gallstone ileus, but there was a suspicion of cholangiocarcinoma. Laparotomy was performed. A perforation of terminal ileum was identified in the mesenteric border of the terminal ileum and adjacent to ileocecal valve, and it was wrapped by omentum. A small 1.5 cm sized stone was impacted in the mesentery at the site of the perforation. The perforation site was closed. Cholecystectomy and proximal common bile duct resection with Roux-en-Y choledochojejunostomy was then performed. (J Korean Surg Soc 2007;72:254-257) KCI Citation Count: 1